2022
DOI: 10.1159/000525252
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus Encephalitis in an Immunocompetent Adult with Disseminated Cutaneous Herpes Zoster after Testosterone Booster Supplements: Case Report

Abstract: Disseminated zoster affects immunocompromised individuals and has a nondermatomal distribution. We report a 28-year-old male who initially presented to the dermatology clinic with pinprick sensation over the right side of his face that was followed by vesicular eruption. Upon which he was diagnosed with herpes zoster and discharged on topical mupirocin ointment three times a day for 7 days and valacyclovir 1 g oral three times a day. A few hours later, he presented to the emergency department with drowsiness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…12 Since that analysis in 2022 one additional patient has been reported. 13 A study looking at hospital visits by patients in Canada prior to 2016 found 2 immunocompetent patients per million had disseminated zoster. 14 A phase 3 trial of the recombinant subunit zoster vaccine in immunocompetent subjects found reduced rates of herpes zoster complications with none of the vaccinated individuals developing disseminated zoster and 0.042% of the unvaccinated individuals developing disseminated zoster.…”
Section: Fig-1: Large Ulcerated Plaque With Irregular and Hyperpigmen...mentioning
confidence: 99%
“…12 Since that analysis in 2022 one additional patient has been reported. 13 A study looking at hospital visits by patients in Canada prior to 2016 found 2 immunocompetent patients per million had disseminated zoster. 14 A phase 3 trial of the recombinant subunit zoster vaccine in immunocompetent subjects found reduced rates of herpes zoster complications with none of the vaccinated individuals developing disseminated zoster and 0.042% of the unvaccinated individuals developing disseminated zoster.…”
Section: Fig-1: Large Ulcerated Plaque With Irregular and Hyperpigmen...mentioning
confidence: 99%